2023
DOI: 10.3390/cancers15123103
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Migrants: A Population-Based Study in Italy

Abstract: Background: Migrants are a vulnerable and neglected population. We aimed at investigating cancer proportionate rates in migrants in Sicily, Southern Italy. Methods: We extracted data on new cancer cases diagnosed between 2004 and 2019 from the Eastern Sicily cancer registry. We compared the adjusted proportionate morbidity ratio (PMR) for the most common cancer types among migrants and non-migrants. We fitted multivariate logistic regression models comparing one cancer to all other cancers to calculate odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
3
1
0
Order By: Relevance
“…We observed a higher risk of cervical cancer among women from Eastern Europe, which might be explained by the high prevalence of HPV infection in that region ( 28 ). This finding is in line with other Italian studies ( 10 , 11 ). In Italy was also reported that 58% Eastern European vs. 19% of Italy-born women are HPV-positive ( 29 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We observed a higher risk of cervical cancer among women from Eastern Europe, which might be explained by the high prevalence of HPV infection in that region ( 28 ). This finding is in line with other Italian studies ( 10 , 11 ). In Italy was also reported that 58% Eastern European vs. 19% of Italy-born women are HPV-positive ( 29 ).…”
Section: Discussionsupporting
confidence: 94%
“…We observed a reduced risk of liver cancer in foreign-born men, especially those coming from South Central America and Eastern Europe, but not in women. These results are in line with another study conducted in Italy ( 10 ). Chronic infection with hepatitis B virus (HBV) or hepatitis C virus (HCV), alcohol abuse, and obesity are all risk factors associated with liver cancer, and they may be differently present in the foreign-born population, as well as according to sex.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, cancer patients who are at risk of experiencing greater disparities are those with lower socioeconomic status, who are frequently from ethnic minority backgrounds. 4 , 5 Secondly, differences in healthcare infrastructure and accessibility, variations in insurance coverage, cultural and language barriers, and disparities in cancer screening and prevention programs can all play a significant role in creating disparities. 6 , 7 Furthermore, it is important to recognize the geographic dimension of disparities in cancer, as evidenced by various studies.…”
Section: Introductionmentioning
confidence: 99%